Comparison of Chu’s Proportion Gauge with a T-bar Tip and a Two-Tip Compass in the Determination of Anterior Dentition Tooth Size in a Group of Puerto Ricans - Murillo, Margarita; Elías-Boneta, Augusto R.; García-Rodríguez, Omar; Toro, Milagros J. (Puerto Rico Health Sciences Journal, 2020)
Objective: Compare maxillary anterior dentition measurements, using Chu’s proportion gauge with a T-bar tip (PG-TT) and a Two-Tip Compass (T-TC), in a group of Puerto Ricans, to determine the reliability of the PG-TT. Methods: This cross-sectional study was conducted at the University of Puerto Rico, School of Dental Medicine, Medical Sciences Campus. The participants (18−35 years old) were dental students or employees of the university. Previously, the examiner had been trained and calibrated in instrument usage. Calibration participants (n = 16) received an oral exam, prophylaxis, and a chlorhexidine mouthwash for home use. After 3 days, the upper-anterior teeth were measured using the 2 instruments. The agreement was determined using weighted kappa statistics (Kw), and 0.80 was the minimum acceptable level. The examiner achieved almost perfect agreement (inter-examiner KwT-TC = 0.95 [0.96−0.93]; KwPG-TT = 0.82 [0.81−0.87]) with a reference examiner. Results: Fifty participants (25 women and 25 men) were evaluated. Length: The teeth of the men presented an unacceptable level of agreement, except for in the right central incisors. For the women, a strong level of agreement was observed only in the lateral incisors and left canines. When the teeth of both sexes were considered, a strong level of agreement was detected, except for in the right canines and left central incisors. Width: The level of agreement was unacceptable, except for in the right canines (distal). Conclusion: T-TC is a more reliable instrument to measure tooth dimensions as compared to the PG-TT.